Results from a Secondary Data Analysis Regarding Satisfaction with Health Care among African American Women Living with HIV/AIDS. Issue 5 (19th August 2014) - Baker, Jillian Lucas; Rodgers, Caryn R. R.; Davis, Zupenda M.; Gracely, Edward; Bowleg, Lisa
ABSTRACT Objective To analyze satisfaction with health care among African American women living with HIV/AIDS. Design Secondary analysis of baseline data of African American women who participated in Protect and Respect, a sexual risk reduction program for women living with HIV/AIDS Setting HIV Care Clinic in an urban city in the northeast United States. Participants One hundred fifty‐seven (157) African American women living with HIV/AIDS. Methods Regression analyses were used to examine the relationships between demographic variables, self‐reported health characteristics, communication with health care providers, and satisfaction with health care provider. Results A majority of women reported satisfaction with medical services (88%, n = 140). Communication with health care providers, detectable viral load, education, income, self‐reported health status, and sexual orientation were significantly bivariately associated with satisfaction with healthcare (all ps < .05). In the multivariate models, no variables significantly predicted satisfaction with healthcare. Conclusion Because satisfaction with health care can influence the quality of care received, health outcomes, and adherence to provider recommendations among patients living with HIV/AIDS, health care providers' ability to elicit satisfaction from their patients is just as important as the services they provide. This project is one of the first studies to find high rates of satisfaction with health care among African American women living with HIV/AIDS. Further examination of satisfaction with health care among African American women living HIV/AIDS may help in narrowing health care disparities and negative treatment outcomes.